Jak nas czytają za granicą? Ankieta - Janiszewski, Aleksander (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
Responding to the questionnaire, the researcher discusses his interests and the specifics of Polish literature reception in the Ukrainian academic circles. He also points out the key features of Polish literature. He mentions the tangible tension between focusing on the locality, the specifics of life in Eastern Europe the global perspective. The researcher draws attention to the fact that in order to understand many of the works the reader must be highly knowledgeable about history.